Diversity, distribution patterns and trophic structure of shallow reef fish assemblages in different reef areas in central and southwest Philippines - Felix, Lucas Ramada (2023)
This study performed different community analyses to examine how different environmental factors are related to the patterns in species diversity, composition, abundance, and biomass of reef fish assemblages from reef areas in Central and Southwest Phillipines surveyed from 2010 to 2019 using underwater fish visual census. This study also provides insights on the impact and efficacy of protective management on the biomass and trophic structure in three reef areas in the country under different levels of fishing pressure. A total of 627 reef fish species belonging to 55 families were recorded in 50 sites surveyed in this study. This recorded number of species represents around 87% of the total reef fish species reported in the country. among the most diverse families were Labridae (104 species) and Pomacentridae (102 species), followed by families Chaetodontidae and apogonidae, each with 39 species. The overall mean species richness was 60.7 species∙500m². The species-area showed the highest slope, and thus the highest diversity, in the Sulu Archipelago, with mean species richness of 77.3 ± 10 species∙500m². In contrast, the lowest slope and lowest mean species richness (39.5 ± 18 species∙500m²) was observed in the Visayas Region, where mean fisher density was also the highest (98.4 ± 42.1 fishers∙km¹). This is consistent with spatial dversity patterns of fisheries-targeted fish families (Serranidae, Lutjanidae, Lethriridae, Haemulidae, Acanthuridae, Signidae), indicator fish (Chaetodontidae) and roving herbivores (Acanthuridae and Scaridae), which showed lowest range of values within this region. Species richness and biomass values for the less exploited families (Pomacentridae and Apoogonidae) did not differ between regions. Reef fish abundance was dominated by families Pomacentridae (57%), Apogonidae (10%), and Labridae (9%), while Pomacentridae (10%), Scaridae (12%), and Acanthuridae (11%) were the most abundant in terms of biomass. The msot abundant species were Pomachromis richardsoni (9%), Acanthochromis polyacanthus (7%), and Pomacentrus alexanderae (4%), while Caesio teres (5%), Siganus guttatus (4%), and Scarus rivukatus (4%) in terms of biomass. Although the overall mean fish abundance (1329.0 ind∙500m²) and biomass (28.9 mt∙km²) were considered high, 71.2% (42 sites) showed values below half the levels found in typical pristine reef areas. Multivariate data analysis showed that not only the diversity, but also the fish assemblage structure in the Visayas Region was different from those in other regions, revealing fisher density and storm frequency as the principal contributors, with Halichoeres nigrescens, Pomacentrus littoralis, and Pomacentrus cureatus being indicative species of reefs under such conditions. Fishing pressure had profound effect on reef fish biomass, showing a significant cumulative increase through time in MPAs located in lightly fished areas, and a gradual decrease in those located in heavily fished areas. These trends also resulted in significant changes in reef fish assemblage trophic structure. Overall, this study contributed to additional knowledge on how the composition and distribution of reef fish assemblages in the Philippines are related to different environmental factors. It also demonstrated the influence of overfishing on their large-scale geographic distribution, diversity patterns and their trophic structure. Lastly, this study confirms the effectiveness of MPAs in lightly fished areas and the applicability of cumulative relative biomass trophic level spectra (BTLS) as an ecological indicator for recovery of protected reefs.
Thesis (M.S. Biology) -- [Miagao, Iloilo] : University of the Philippines Visayas, January2023.